2007
DOI: 10.14356/kona.2007008
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Wetting and Dewetting Behavior of Powders

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 32 publications
0
13
0
1
Order By: Relevance
“…At pH 4, the contact angle was determined to be about 150°, in alkaline solutions it decreased to 100°, and so these measurements turned out to be much more sensitive to pH (to electrical charge at solid/liquid interface). In the further analysis of these data, Chander et al (2007) showed an excellent correlation between molybdenite oil flotation recovery and oil/water contact angle of molybdenite ( Fig. 6) (in oil flotation an oil phase is substituted for the gaseous phase).…”
Section: Polymers In Flotation Of Molybdenitementioning
confidence: 86%
See 1 more Smart Citation
“…At pH 4, the contact angle was determined to be about 150°, in alkaline solutions it decreased to 100°, and so these measurements turned out to be much more sensitive to pH (to electrical charge at solid/liquid interface). In the further analysis of these data, Chander et al (2007) showed an excellent correlation between molybdenite oil flotation recovery and oil/water contact angle of molybdenite ( Fig. 6) (in oil flotation an oil phase is substituted for the gaseous phase).…”
Section: Polymers In Flotation Of Molybdenitementioning
confidence: 86%
“…Also plotted is the effect of pH on the oil/water contact angle of molybdenite, expressed in terms of the flotation dewetting relation ð1 À cos hÞ(Chander et al, 2007).…”
mentioning
confidence: 99%
“…The water adsorption tests and water contact angle (WCA) evaluations of uncoated and PPT-coated silica particles were carried out according to the Washburn capillary rise method [40]. A dynamic contact angle meter (DCAT21, Dataphysics) equipped with a Wilhelmy balance controlled by SCAT software was utilized.…”
Section: Washburn Capillary Rise Testsmentioning
confidence: 99%
“…Prior to each measurement, the cell was ultrasonicated in acetone and hexane and rinsed with Milli-Q water followed by drying at 100°C for 1 h. The packed cell with 4 g of particles was placed in close contact with water, and the mass of water adsorbed into the bed of particles was recorded as a function of time. Weight square (m 2 ) values of adsorbed water versus time (t) were plotted and utilized to calculate the WCA of particles according to the Washburn equation [40]:…”
Section: Washburn Capillary Rise Testsmentioning
confidence: 99%
See 1 more Smart Citation